Avaliaç\~ao do impacto dos empréstimos dos fundos constitucionais destinados ao financiamento do PRONAF nos municípios das regi\~oes norte, nordeste e centro-oeste - Márcio Bruno Ribero (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This paper aims to evaluate empirically the economic effects of loans from Constitutional Financial Funds to the National Program for Strengthening Family Agriculture (Pronaf) in the municipalities of their respective regions. In addition to the data of those loans for the period 2012-2016, we used indicators of employment and production of family farming, together with a set of covariates that characterize these establishments in each municipality, obtained from the information available in the 2006 and 2017 Brazilian Agricultural Censuses. Our results from generalized propensity score and dose-response functions estimates indicated positive and statistically significant marginal effects only for the Northeast Constitutional Fund (FNE), and within a range of values that suggests the existence of minimum, maximum and optimal levels for the average intensity of its loans.
Keywords: R58; R51; C52; 330; constitutional financial funds; National Program for Strengthening Family Agriculture; impact evaluation; dose-response function